The implications of cross-national policies for the relative incomes of families with children by family structure and parental education - Stephanie Moller; Joya Misra; Elizabeth Wemlinger; Eiko Strader (Luxembourg Income Study (LIS), 2013)
Focusing on an array of European and North American welfare states between 1985 and 2005, we consider how welfare state policies are related to households' relative incomes, taking into account cross-national and temporal differences in income distributions. At the same time, we consider how two of the central factors that may be driving income inequality at the individual or household level - parental educational level and family structure - may be related to a household's relative income. This research fills a gap in the literature because there are surprisingly few studies that examine inequality by both family structure and education, and even fewer that examine relative income cross-nationally and longitudinally. Theoretically, our contributions are to structural vulnerability theory. Structural vulnerability theory aims to consider how the individual, or the household, is structurally located within a context. Our analysis provides a better test of structural vulnerability theory than previous studies because structural vulnerability is operationalized in both the independent (through cross-level interactions) and dependent variables. By creating a dependent variable that standardizes household income relative to both median income and societal-level income inequality, we are able to get at the very center of structural vulnerability.
Keywords: 330; Sozialpolitik; Einkommensverteilung; Bildungsniveau; Gini-Koeffizient; Strukturgleichungsmodell; Europa; Nordamerika